Constructions of masculine sexuality, high risk sex and HIV/AIDS amongst young Xhosa men in South Africa - Mehlomakulu, Vuyelwa (Stellenbosch : Stellenbosch University, 2008)
Thesis (MA (Psychology))--Stellenbosch University, 2008.